Differential Role of NKG2A/HLA-E Interaction in the Outcomes of Bladder Cancer Patients Treated with M. bovis BCG or Other Therapies - Inmaculada Ruiz-Lorente; Lourdes Gimeno; Alicia López-Abad; Pedro López Cubillana; Tomás Fernández Aparicio; Lucas Jesús Asensio Egea; Juan Moreno Avilés; Gloria Doñate Iñiguez; Pablo Luis Guzmán Martínez-Valls; Gerardo Server; Belén Ferri; José Antonio Campillo; et al. (Biomedicines)
Background: Immunotherapy is gaining great relevance in both non-muscle-invasive bladder cancer (NMIBC), with the use of bacille Calmette–Guerin (BCG), and in muscle-invasive BC (MIBC) with anti-checkpoint therapies blocking PD-1/PD-L1, CTLA-4/CD80-CD86, and, more recently, NKG2A/HLA-E interactions. Biomarkers are necessary to optimize the use of these therapies. Methods: We evaluated killer-cell immunoglobulin-like receptors (KIRs) and HLA-I genotyping and the expression of NK cell receptors in circulating T and NK lymphocytes at diagnosis in 325 consecutive BC patients (151 treated with BCG and 174 treated with other therapies), as well as in 648 patients with other cancers and 973 healthy donors as controls. The proliferation and production of cytokines and cytotoxicity were evaluated in peripheral blood mononuclear cells, stimulated in vitro with anti-CD3/CD28 or BCG, from selected patients based on HLA-B −21M/T dimorphism (NKG2A ligands). Results: The HLA-B −21M/T genotype showed opposing results in BC patients treated with BCG or other therapies. The MM genotype, compared to MT and TT, was associated with a longer 75th-percentile overall survival (not reached vs. 68.0 ± 13.7 and 52.0 ± 8.3 months, p = 0.034) in BCG, but a shorter (8.0 ± 2.4 vs. 21.0 ± 3.4 and 19.0 ± 4.9 months, p = 0.131) survival in other treatments. The HLA-B −21M/T genotype was an independent predictive parameter of the progression-free survival (HR = 2.08, p = 0.01) and the OS (HR = 2.059, p = 0.039) of BC patients treated with BCG, together with age and tumor histopathologic characteristics. The MM genotype was associated with higher counts of circulating CD56bright, fewer KIR2DL1/L2+ NK cells, and lower NKG2A expression, but not with differential in vitro NK cell functionality. Conclusions: The HLA-B −21M/T is independently associated with BC patient outcomes and can help to optimize the use of new immunotherapies in these patients.